KEBEBASAN HAKIM DALAM MENJATUHKAN PIDANA MINIMUM DAN MAKSIMUM PADA TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN - Nursolihi Insani (The Juris, 2023)
In the Indonesian Criminal Code (KUHP), there is no minimum sanction for a criminal offense. However, the KUHP provides a limitation in book one on general rules, which states that the shortest prison sentence is one day and a maximum of fifteen years. This will lead to legal uncertainty, if it turns out that aggravated criminal offenses must also refer to Article 12 of the Criminal Code to determine the minimum sanction. The point here is, there is no difference in the end between the crime of ordinary theft and the crime of theft with aggravation, if in the end it is sentenced under the maximum penalty for ordinary theft or theft in the main form. The research method used is a literature study or also called normative, with a statutory approach, using primary and secondary legal materials which are then read, recorded, then summarize all materials related to the theme of the writing raised. In the end, judges as law enforcers who have the freedom to decide a case, must rely on a clear and firm rule of law, when a rule of law does not provide firmness, the final result in the decision will provide legal uncertainty for the litigants.